Asymptomatic malaria parasitaemia and virological non-suppression among children living with HIV in a low transmission area in Accra, Ghana: a cross-sectional study - Afrane, A.K.A.; Alhassan, Y.; Amoah, L.E.; Nyarko, M. Y.; Addo-Lartey, A. (BMC Infectious Diseases, 2024)
Background Human Immunodeficiency Virus (HIV) and malaria are two major diseases in sub-Saharan Africa. Co-infection can significantly impact the clinical outcomes of both conditions. We assessed the proportion of HIV infected children at Korle Bu Teaching Hospital (KBTH) and Princess Marie Louise Hospital (PML) with malaria parasites. The association between asymptomatic malaria parasitaemia and virological non-suppression was also determined in these children. Methods This cross-sectional study of 277 asymptomatic malaria in children receiving care at paediatric HIV clinics at KBTH and PML was conducted from September to November 2022. Patients who had been on antiretroviral therapy (ART) for at least six months were eligible to participate. Structured questionnaires were used to collect socio-demographic information, malaria prevention behaviors, and ART-related data using in-person interviews. Microscopy and PCR were used to screen for malaria, and GeneXpert was used to determine viral load. To examine the determinants of malaria PCR positivity and virological non-suppression, chi-square tests and logistic regression were performed. Results The median age of the participants was 9 years (range: 6–12 years). Males comprised 158 (57%) of the study population. We detected 10 (3.6%) and 21 (7.6%) malaria cases by microscopy and PCR, respectively. Virological non-suppression (VL>1000 copies/ml) was observed in 82 (29.6%) of the 277 participants. Among the suppressed individuals, 62 (22.4%) exhibited low-level viraemia (VL level 40-1000 copies/ml) and 133 (48%) had undetectable viral load levels. No factors were associated with the presence of malaria PCR positivity carriage. Poor adherence to ART was associated with a five-fold increase in the risk of viral load non-suppression (AOR=4.89 [CI=2.00-11.98], p=0.001). Conclusion The proportion of children living with HIV with asymptomatic malaria parasitaemia was low. Approximately one-third of the study population had virological non-suppression. The interaction between malaria parasitemia and viral replication may not be the main cause for virological non-suppression in this low transmission area
Research Article
Keywords: Antiretroviral therapy; Asymptomatic malaria; Parasitaemia